On The Role Of The Scientific Heritage Of The Orientalist Y.E. Bertels In The Development Of Medieval Philosophy (Texas Journal of Multidisciplinary Studies, 2025)
The article reveals the contribution of the great thinker Abdurrahman Jami to the formation and development of medieval philosophical, socio-political ideas based on the scientific research of Y.E.Bertels. At the same time, the scientist's scientific and philosophical views are discussed. Jami's religious-mystical and educational views, their place and importance in social life are revealed